FAKTOR YANG MEMPENGARUHI GURU PEMBIMBING DALAM MEMILIH METODE PADA LAYANAN INFORMASI DI SMK NEGERI SE-KOTA PADANG - Hazwary, Ezhiana Faika; Kasih, Fitria; Yusnetti, Yusnetti (Bimbingan dan Konseling, 2013)
The problem in this study is: What is the factors that influenced a tutor in selecting information services at SMK N whole the city of Padang. This study aimed to describe: 1) The factors influenced the tutor to choose a information services method which is seen by the objectives to be achieved, 2) The factors influenced tutor chosen the information service method taken by material services, 3) The factors influenced the tutor choose the information services method viewed by the learners, 4) The factors influenced the tutor to choose a information services method seen by situation, 5) The factors influenced tutor in choosing the method of information services viewed by the teacher. This research is a descriptive study describing the real situation. The population is 38 people learners. Sampling in this study using the sampling technique the total subjects in this study were all teachers as mentors SMK Padang city, amounting to as many sas 38 people. Collecting data instrument used a questionnaire, while data analysis techniques using percentage analysis. The results of the study found that: 1) The factors influenced the tutor to choose a method of information services seen from the goals to be achieved in the large category, 2) The factors influenced tutor chosen the information service of material service visits are in the large category, 3) The factors influenced the tutor to choose a method of information services seen from students in the large category, 4) The factors influenced the guidance counselor to choose the information services method seen by situation in the large category, 5) The factors influenced the tutor to choose the information services method in the large category. For a guidance counselor recommended to improve the skills and insights in the implementation of activities, especially in information services